KOMUNIKASI WORD OF MOUTH DALAM PENGEMBANGAN DESA WISATA SAMIRAN BOYOLALI - Setiawan, Feri; Hartini, Sri; Putro, Fanny Hendro Aryo (Kinesik, 2022)
Samiran Boyolali Tourism Village (Dewi Sambi), is a tourist village located in Selo District, Boyolali Regency. Dewi Sambi was established in 2007. Dewi Sambi has experienced very rapid development, seen from the increase in tourist attractions, the increase in homestays and the ability of existing human resources to increase. Dewi Sambi's very rapid development is inseparable from good Marketing Communication. The marketing activities carried out by Dewi Sambi's management are through a word of mouth approach. This communication strategy is effective and has a positive impact on the development of Dewi Sambi. The steps taken by Dewi Sambi's management in marketing is that Dewi Sambi's management invites and invites tourism service providers or tourism bureaus to provide information regarding Dewi Sambi's existence, products, as well as accommodation and costs at Dewi Sambi. in addition, by sending letters to the agencies in Boyolali Regency.